(3GdJMcje GdeJYOO GdCWQGa aj YbhO GdJLGQI GdOhdjI Hjf GdfXQjI h GdJWHjb (B/ s - (3YdGA eMHhH Ydi GdLRGQs; (3SGej YHOGdHGbj eMeO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3JYQV GdOQGSI deaghe GdJMcje hfXGeg GdbGfhfj(B. (3Ke ddMGdGJ GdJj dG JYHQ Yf GdJMcje GdJLGQj GdeJYOO GdCWQGa Ke ddMGdGJ GdJj jJMbb ajgG gPG GdfhY ef GdJMcje hGdfGLeI Yf JYOO CWQGa GJaGb GdJMcje Ch Yf GfJbGdg hab GdbhGYO GdYGeI aj GdbGfhf Ch GeJOGOg YHQ eLehYI GdTQcGJ Ch GdYbhO(B. (3Ke dJONd hEONGd GdZjQ Ch Ve GdJMcjeGJ cCSHGH dgPG GdJYOO hehba Gdabg hGdJTQjYGJ efg(B. (3Ke dHjGf HYV GdBKGQ GdfGLeI Yf JYOO CWQGa GdJMcje Ydi eSCdI GdbGfhf GdhGLH GdJWHjb hJTcjd gjFI GdJMcje aj GdJMcje GdeJYOO GdCWQGa hHYV GdedGeM GdELQGFjI aj GdJMcje GdeJYOO GdCWQGa hGdeJYdbI HGdOYhi GdYGHQI(B: (3hHGdOYhi ZjQ GdeHGTQI hHGdOYhi GdeHGTQI ef GdebGhd ef GdHGWf VO UGMH GdYed hHGdeSFhdjI GdJVGefjI Yf GdOjhf GdeSJMbI Ydi GdTQcI aj EWGQ eLehYI GdTQcGJ hGdebGUI HjfgG hHYV GdYbHGJ GdELQGFjI GdeMJedI aj GdJMcje GdeJYOO GdCWQGa hebJQMGJ ehGLgJgG Ke JfGhdJ GdQSGdI GdMce aj GdJMcje GdeJYOO GdCWQGa ef MjK EUOGQg hMLjJg hHWdGfg GdeJYdb HGdENdGd HMb GdOaGY Ch HeNGdaI GdfXGe GdYGe hCNjQkG GNJJeJ Jdc GdOQGSI HNGJeI PcQ ajgG HYV GdfJGFL GdJj NdUJ EdjgG(B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B384-406s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GfJbGd GJaGb GdJMcjes; (3eLehYI GdYbhO s; (3eLehYI GdTQcGJs; (3Ve GdJMcjeGJs; (3JYOO GWQGa GdJMcje s; (3GdOYhi ZjQ GdeHGTQIs; (3HWdGf Mce GdJMcje s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs